2021
DOI: 10.3390/agronomy11050912
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Level and Genetic Parameters for Phenotypic Traits in Bermudagrass (Cynodon spp.) Germplasm

Abstract: Bermudagrass (Cynodon spp.) is a forage and turf crop commonly used worldwide. The USDA bermudagrass germplasm set is composed of plant introductions (PI’s) collected around the world and contains different Cynodon species, primarily C. dactylon. The collection was screened in a replicated trial in Florida for forage yield, leaf width, nutritive value (NV), and Bermudagrass Stem Maggot (Atherigona reversura) (BSM), which is an invasive pest to the southeastern United States that damages bermudagrass fields. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…As a cross-pollinating plant, wild germplasms of C. dactylon collected at different regions usually show enormous genetical and morphological variations ( Wu et al, 2004 , 2007 ; Farsani et al, 2012 ; Tan et al, 2014 ; Zheng et al, 2017 ). Karyotype and molecular marker analyses not only revealed that polyploidy and aneuploidy events exist in C. dactylon but also pointed out the genome of C. dactylon is highly heterozygous ( Wu et al, 2006 ; Chaves et al, 2019 ; Grossman et al, 2021 ). These characteristics make C. dactylon an interesting plant material to investigate genome stability, variability, and evolution ( Khanal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a cross-pollinating plant, wild germplasms of C. dactylon collected at different regions usually show enormous genetical and morphological variations ( Wu et al, 2004 , 2007 ; Farsani et al, 2012 ; Tan et al, 2014 ; Zheng et al, 2017 ). Karyotype and molecular marker analyses not only revealed that polyploidy and aneuploidy events exist in C. dactylon but also pointed out the genome of C. dactylon is highly heterozygous ( Wu et al, 2006 ; Chaves et al, 2019 ; Grossman et al, 2021 ). These characteristics make C. dactylon an interesting plant material to investigate genome stability, variability, and evolution ( Khanal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Large genetic variability is present in the core collection (Anderson et al, 2009). The core collection, in addition to several PIs obtained from GRIN, showed significant genetic variation for crude protein (CP), phosphorous concentration (P), in vitro digestible organic matter (IVDOM) and neutral detergent fibre (NDF) (Souza et al, 2020), and for yield and bermudagrass stem maggot (BSM, Atherigona reversura ) tolerance evaluated in Florida (Grossman et al, 2021). However, these two studies were limited to data collected in Florida, and there is a need to include data from other locations to make informed selections and release cultivars adapted to a broad range of environmental and management conditions in the transition zones.…”
Section: Brief History Of Bermudagrass Breedingmentioning
confidence: 99%
“…tolerance evaluated in Florida (Grossman et al, 2021). However, these two studies were limited to data collected in Florida, and there is a need to include data from other locations to make informed selections and release cultivars adapted to a broad range of environmental and management conditions in the transition zones.…”
Section: Brief History Of Bermudagrass Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important warm-season forage and turfgrass, bermudagrass is more variable in genome size and ploidy level, so the genetic and morphological diversity of abundant wild germplasm resources provides different varieties for bermudagrass breeding [ 10 , 11 ]. According to the development levels of shoots and stolons, wild bermudagrass are commonly divided into forage-types and turf-types based on different plant types [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%